Precision medicine based on the phenotypic differences in peripheral T helper cells in patients with psoriatic arthritis: One year follow-up outcomes - Miyagawa, Ippei; Nakayamada, Shingo; Ueno, Masanobu; Miyazaki, Yusuke; Ohkubo, Naoaki; Inoue, Yoshino; Kubo, Satoshi; Tanaka, Yoshiya (Frontiers in Medicine, 2022)
Purpose. We validated the one-year effectiveness of strategic treatment with biological disease-modifying anti-rheumatic drugs (bDMARDs) based on peripheral T-lymphocytic phenotyping and explored the impact of treatment on T helper lymphocytic phenotypes. Methods. Ninety-seven patients were registered in this study. One-year treatment response was compared between the two groups: the strategic bDMARDs treatment group (n = 41), in which bDMARDs were selected based on peripheral blood lymphocyte analysis, and the standard bDMARDs treatment group (n=56), in which the patients underwent no strategic selection of bDMARDs and phenotyping. Changes in helper T lymphocytic phenotypes were evaluated after one-year post-treatment. Results. In the standard bDMARDs treatment group, 23 patients (42.6%) achieved disease activity in psoriatic arthritis (DAPSA)-remission (REM), and 23 of 46 (50.0%) achieved PASI 90. In the strategic bDMARDs treatment group, 22 (53.7%) achieved DAPSA-REM, and 26 of 35 (74.2%) achieved PASI90. The rate of achieving minimal disease activity (MDA) and DAPSA-REM at month 6, DAPSA-low disease activity (LDA) at months 6 and 12, and PASI 90 at month 12 were significantly higher in the strategic bDMARDs treatment group. After treatment with ustekinumab, the proportion of aTh1/CD4 (%) significantly decreased. The percent reduction in activated Th17 cells was significantly higher in IL-17-i cells than in UST/TNF-i cells. Conclusions. The results of this study demonstrate the one-year effectiveness of precision medicine based on peripheral T-lymphocytic phenotyping in terms of DAPSA and MDA. Analysis of data from real-world clinical practice showed that the impact on the immune system varied among bDMARDs. However, because psoriatic arthritis has very high heterogeneity, it may be necessary to conduct studies with a larger sample size, perhaps drawing samples from multiple institutions.